Averted lung cancer deaths due to reductions in cigarette smoking in the United States, 1970–2022 - Farhad Islami; Nigar Nargis; Qinran Liu; Priti Bandi; Rebecca L. Siegel; Parichoy Pal Choudhury; Neal D. Freedman; Kenneth E. Warner; Ahmedin Jemal (CA: A Cancer Journal for Clinicians, 2025)
Abstract Lung cancer mortality rates in the United States have declined steeply in recent decades, largely because of substantial reductions in smoking prevalence, as approximately 85% of lung cancer deaths are attributable to cigarette smoking. In this study, the authors estimate the number of averted lung cancer deaths and corresponding person‐years of life gained during 1970–2022 as a measure of progress in cancer prevention through tobacco control. By using the 1970–2022 National Center for Health Statistics mortality data (with national coverage), the authors calculated the expected number of deaths for each year, age, sex, race, and age group based on the expected lung cancer death rate multiplied by the population at risk in that group. The number of averted lung cancer deaths were calculated by subtracting the observed number of deaths from the expected number in each group. Person‐years of life gained were estimated as a measure of avoided premature mortality based on the average additional years a person would have lived if they had not died from lung cancer. The authors estimated that 3,856,240 lung cancer deaths (2,246,610 in men, 1,609,630 in women) were averted, and 76,275,550 person‐years of life (40,277,690 in men, 35,997,860 in women) were gained during 1970–2022, with an average of 19.8 person‐years of life gained (17.9 in men, 22.4 in women) per averted death. The number of averted lung cancer deaths accounted for 51.4% of the estimated declines in overall cancer deaths and was substantially greater in men (60.1%) than in women (42.7%). By race, this proportion was 53.6% in the White population (62.8% in men, 44.6% in women) and 40.0% in the Black population (44.4% in men, 34.7% in women). The substantial estimated numbers of averted lung cancer deaths and person‐years of life gained highlight the remarkable effect of progress against smoking on reducing premature mortality from lung cancer.